REASON AND REVELATION ACCORDING TO NURCHOLISH MADJID AND IBN SINA - Muhamad Rifki Ramdhani; Abu Khairi; Farhan Alfuadi; Satriadi Satriadi; Nano Warno (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2025)
This research examines Nurcholish Madjid’s conception of reason through the epistemological lens of Ibn Sina’s Peripatetic philosophy. Using a literature-based character study and descriptive-heuristic analysis, the study explores the definition and limits of reason in Nurcholis’s thought. According to him, reason is the activity of thinking, bestowed by Allah upon humans as His caliphs on earth. However, human reason is confined to universal matters; therefore, divine revelation is necessary to guide humans beyond reason’s limits—especially in knowing God. Reason, thus, cannot fully comprehend the Divine. When viewed through Ibn Sina’s Peripatetic epistemology, two conclusions emerge. First, Nurcholis’s definition of reason is largely adequate, as it aligns with Ibn Sina’s view that intellect is a faculty unique to the human soul, distinct from that of plants and animals. Second, Nurcholis’s view is sufficient in its human dimension but limited in the divine one. For Ibn Sina, God is the First Intellect, whose self-contemplation gives rise to subsequent intellects. Hence, within the Peripatetic framework, Nurcholis’s notion of the limits of reason is considered incomplete regarding the divine aspect.